Efficient Parameterized Precoder Tracking in Slowly Time-Varying MIMO Channels - Kolla, Naresh; Appaiah, Kumar; Chopra, Ribhu (IEEE communications letters, 2023)
Precoding in MIMO wireless communication systems is essential for achieving high data rates. However, feeding back precoders places a feedback burden. Exploiting temporal correlation and use of adaptive feedback can significantly reduce the feedback requirement, but even this does not scale well for larger MIMO systems. We propose an approach to partition precoder update parameters, and selectively feed back only those parameters that vary significantly. Specifically, we express precoder variations as zero-diagonal complex matrices whose elements have nearly constant magnitude, thus requiring only phase information. Simulations reveal that this method achieves high rates at 50% lower feedback than prior approaches.